2009
DOI: 10.1074/jbc.m900206200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of myo-Inositol-3-phosphate Synthase Isoforms

Abstract: Myo-inositol is an important constituent of membrane phospholipids and is a precursor for the phosphoinositide signaling pathway. It is synthesized from glucose 6-phosphate by myo-inositol-3-phosphate synthase (IP synthase), a homotrimer composed of a 68-kDa polypeptide in most mammalian tissues. It is a putative target for mood-stabilizing drugs such as lithium and valproate. Here, we show that the rat gene (Isyna1) encoding this enzyme generates a number of alternatively spliced transcripts in addition to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 78 publications
2
32
0
Order By: Relevance
“…Conversely, in testis and pancreas, the digested bands were comparatively more intense than the 3.0-kb band suggesting that the internal Sma I sites are poorly methylated. The observation with the testis is consistent with this tissue expressing high levels of IP synthase [2]. In the heart, all three bands appeared equally pronounced with the 3.0-kb band slightly more intense than the two digested bands.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Conversely, in testis and pancreas, the digested bands were comparatively more intense than the 3.0-kb band suggesting that the internal Sma I sites are poorly methylated. The observation with the testis is consistent with this tissue expressing high levels of IP synthase [2]. In the heart, all three bands appeared equally pronounced with the 3.0-kb band slightly more intense than the two digested bands.…”
Section: Resultssupporting
confidence: 82%
“…We have previously demonstrated that ISYNA1 is upregulated by E2F1 [20], an observation that has been confirmed in yeast [21]. More recently, we demonstrated that Isyna1 generates a number of alternatively spliced isoforms, one of which was shown to negatively modulate enzyme activity [2]. Studies presented here clearly implicate epigenetic mechanisms (DNA methylation) in the tissue-specific expression of Isyna1 .…”
supporting
confidence: 74%
See 2 more Smart Citations
“…For example, in rat, at least eight MIPS variants have been detected either at the mRNA or protein level [23]. In humans, at least four MIPS variants have been observed at mRNA level [43].…”
Section: Discussionmentioning
confidence: 99%